The Legacy of Colonialism and Ecological Genocide on Indigenous People of Nauru - Wardhani, Baiq (Andalas Journal of International Studies (AJIS), 2023)
This paper explains the connection between colonialism, environmental destruction, capitalism, and dependency in Nauru. Nauru is an extreme example of how the legacy of colonialism has had a destructive impact on the indigenous people. In the case of Nauru, Pivot is the collapse of the symbiotic relationship between humans and the environment. There has been limited research on the impact of colonialism and ecological destruction on indigenous people, especially in international relations scholarship. The analysis of Nauru represents a microcosm of the conflict between environmental sustainability and the commercial economy. Nauru has undergone environmental injustice for decades and has delivered a prolonged impact of dietary problems and health crises. I argue that the current Nauruan national crisis and economic stagnation have resulted from its complex history of colonialism and the failure of post-colonial successive governments to escape from the former colonial ruler's structurally induced dependency.